Relationship between adaptation and mitigation of climate change with the climate village program (ProKlim) In Paser Regency - Anshari, Syafruddin; Listyarini, Sri; Nurmawati, Subekti (Universitas Pakuan, 2023)
This study aims to understand the relationship between the Climate Village Program (ProKlim) success rate and climate change adaptation and mitigation actions in Paser Regency. The results of the analysis showed that simultaneously climate change adaptation actions had a real effect on the success rate of ProKlim in Paser Regency by 81.45% with a significance level of 0.00054 (less than α = 0.05), while climate change mitigation actions have a real effect on the success rate of ProKlim in Paser Regency by 83.66% with a significance level of 0.0052 (less than α = 0.05). Meanwhile, the relationship of adaptation actions to the success rate of the ProKlim in Paser Regency is partially influenced by the efforts of control of climate change-related diseases with a significant level of 0.0305 (less than α=0.05). Meanwhile, climate change mitigation actions, it is partially influenced by low-emission agricultural cultivation efforts with a significant level of 0.0305 (less than α=0.05). Thus, the efforts to achieve the success of ProKlim cannot be done partially but must be carried out comprehensively because the impact of climate change has been felt in all aspects so it is necessary to apply all variables of climate change adaptation and mitigation sustainably.ABSTRAKPenelitian ini bertujuan untuk memahami hubungan tingkat keberhasilan Program Desa Iklim (ProKlim) dengan aksi adaptasi dan mitigasi perubahan iklim di Kabupaten Paser. Hasil analisis menunjukkan bahwa secara simultan aksi adaptasi perubahan iklim berpengaruh nyata terhadap tingkat keberhasilan ProKlim di Kabupaten Paser sebesar 81,45% dengan tingkat signifikansi 0,00054 (kurang dari α = 0,05), sedangkan aksi mitigasi perubahan iklim mempunyai pengaruh nyata terhadap keberhasilan ProKlim di Kabupaten Paser. berpengaruh terhadap tingkat keberhasilan ProKlim di Kabupaten Paser sebesar 83,66% dengan tingkat signifikansi 0,0052 (kurang dari α = 0,05). Sedangkan hubungan tindakan adaptasi terhadap tingkat keberhasilan ProKlim di Kabupaten Paser sebagian dipengaruhi oleh upaya pengendalian penyakit terkait perubahan iklim dengan tingkat signifikansi sebesar 0,0305 (kurang dari α=0,05). Sedangkan tindakan mitigasi perubahan iklim, sebagian dipengaruhi oleh upaya budidaya pertanian rendah emisi dengan tingkat signifikan sebesar 0,0305 (kurang dari α=0,05). Dengan demikian, upaya untuk mencapai keberhasilan ProKlim tidak dapat dilakukan secara parsial melainkan harus dilakukan secara komprehensif karena dampak perubahan iklim sudah terasa di seluruh aspek sehingga perlu diterapkannya seluruh variabel adaptasi dan mitigasi perubahan iklim secara berkelanjutan.